Analisis pengelolaan Jurnal Polynom sebagai Wadah Publikasi Karya Tulis Mahasiswa - Ramadani, Iqbal; Nurtiyasari, Devi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
A scientific journal can be interpreted as the outcome of studies or research published periodically through educational and research institutions. Polynom is a journal from the mathematics education program, specifically serving as a platform for student publications, particularly those from the mathematics education program at UIN Sunan Kalijaga. However, the Polynom Journal, as a platform for student scientific publications, does not simply publish student works without a quality review process. This is because it will impact the accreditation of the journal itself. The purpose of this research is to understand the management strategies of the Polynom journal as a student journal that adheres to National Journal Accreditation and Program Accreditation. The research method used is descriptive qualitative. The researcher carried out several research steps, including collecting data from the Polynom journal's dashboard, interviewing journal managers, and analyzing data. The Polynom Journal, as a student journal, has implemented strategies that adhere to national journal accreditation and program accreditation. However, the applied strategies have not been fully implemented. The peer reviewers at the Polynom Journal are already more than 50% from outside UIN Sunan Kalijaga, but the manuscript reassessment process has not yet been fully implemented. There is already a publication workflow, but it has not run optimally. Nevertheless, the Polynom Journal has established good writing guidelines, consistent writing style, and good regularity.